Defining the safe corridor for transcondylar screw placement in the feline humeral condyle. Issue 12 (December 2022) - Simpson, Matthew; Meeson, Richard
Objectives: The aim of this study was to develop guidelines for the optimal location of drill entry and exit points for insertion of a transcondylar screw across the feline humeral condyle. Methods: Multiplanar reconstruction of feline elbow CT scans performed between 2016 and 2021 at one referral institution were reviewed. The optimum medial and lateral epicondylar entry and exit points for transcondylar screw placement were determined. These values were normalised to the humeral condylar diameter (HCD) for each elbow to determine the transcondylar screw placement guidelines. These guidelines were applied to each elbow and tolerance angles were determined in the transverse and frontal plane CT images to determine the safe corridor for screw placement. Results: Twenty elbows from 12 cats were evaluated in this study. The guidelines for transcondylar screw placement were as follows: the medial entry/exit point was 0.38 × HCD cranial and 0.16 × HCD distal to the medial epicondyle, and the lateral entry/exit point was 0.3 × HCD cranial and 0.16 × HCD distal to the lateral epicondyle. Tolerance angles were statistically significantly ( P <0.05) larger in both frontal (34.5% larger) and transverse (21.1% larger) planes when drilled from a lateral to medial direction compared with drilling from a medial to lateral direction. Conclusions and relevance: The guidelines determined from this study may aid clinicians in the placement of humeral transcondylar screws in cats. Where possible, drilling from a lateral to medial direction is recommended owing to the higher tolerance angles reducing the likelihood of articular surface damage. Further studies are warranted to determine whether these guidelines are clinically useful and result in the safe insertion of a transcondylar screw in the clinical setting.